2012
DOI: 10.1016/j.limno.2011.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Emergence patterns and microhabitat preference of aquatic dance flies (Empididae; Clinocerinae and Hemerodromiinae) on a longitudinal gradient of barrage lake system

Abstract: a b s t r a c tAquatic dance flies (Empididae; Clinocerinae and Hemerodromiinae) are important components of freshwater assemblages, especially in running waters. They are predators as larvae and adults and thus essential for understanding aquatic food webs. This study was conducted in Plitvice lakes National Park (Croatia) representing a wide variety of freshwater habitats (springs, streams, lakes and tufa barriers). Adults were collected monthly from March 2007 until March 2009 using pyramid-type emergence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 21 publications
2
31
0
Order By: Relevance
“…low water temperature and high oxygen concentration; Hynes, 1976;Fochetti and Tierno de Figueroa, 2008;Zwick, 2011) and the wide range of suitable habitats (Riđanović and Božićević, 1996;Miliša et al, 2010). The differences in abundance and taxa richness between the two studied years could be attributed to the variability of environmental conditions, especially water temperature and discharge, as already shown in some other studies (Zwick, 2011;Ivković et al, 2012Ivković et al, , 2014Vilenica et al, 2017a). As the majority of stonefly species prefer the headwaters of lotic habitats (Graf and Schmidt-Kloiber A, 2003;Graf et al, 2009Graf et al, , 2017, taxa richness generally decreased downstream as expected and supported by preliminary studies (Vannote et al, 1980;Sivec, 2009, 2011b).…”
Section: Stonefly Assemblages and Relationships With Environmental Vasupporting
confidence: 60%
See 2 more Smart Citations
“…low water temperature and high oxygen concentration; Hynes, 1976;Fochetti and Tierno de Figueroa, 2008;Zwick, 2011) and the wide range of suitable habitats (Riđanović and Božićević, 1996;Miliša et al, 2010). The differences in abundance and taxa richness between the two studied years could be attributed to the variability of environmental conditions, especially water temperature and discharge, as already shown in some other studies (Zwick, 2011;Ivković et al, 2012Ivković et al, , 2014Vilenica et al, 2017a). As the majority of stonefly species prefer the headwaters of lotic habitats (Graf and Schmidt-Kloiber A, 2003;Graf et al, 2009Graf et al, , 2017, taxa richness generally decreased downstream as expected and supported by preliminary studies (Vannote et al, 1980;Sivec, 2009, 2011b).…”
Section: Stonefly Assemblages and Relationships With Environmental Vasupporting
confidence: 60%
“…Higher water temperatures were already recorded as causing an earlier start in emergence (Illies, 1971;Harper and Peckarsky, 2006;Zwick, 2011). Several long-term studies have shown that discharge patterns are one of the most important factors influencing changes in aquatic insect assemblages between years (Wagner and Schmidt, 2011;Ivković et al, 2012Ivković et al, , 2014Vilenica et al, 2017a). Differences in stonefly abundances between the two studied years could therefore be related to a higher discharge in 2008 which caused a more prominent downstream larval drift (Sertić Perić et al, 2011), resulting in a lower number of emerging adults.…”
Section: Stonefly Emergence Patterns and Abundancementioning
confidence: 98%
See 1 more Smart Citation
“…In one spring (Pecki spring, Banovina region) (Table 1) we installed 5 pyramid-type emergence traps in 2010 and 2011 to investigate the emergence dynamics of caddisflies (Figure 1). This investigation is part of a multi-year study on emergence dynamics of aquatic insects in springs and other aquatic habitats in Croatia and the Dinaric karst of the Balkan Peninsula (Bosnia and Herzegovina) (Kučinić 2002, Previšić et al 2007, Ivković et al 2011, Semnički et al 2011, 2012, M. Kučinić unpublished data). The emergence trapping methodology was presented in detail by Kučinić (2002) and Previšić et al (2007).…”
Section: Methodsmentioning
confidence: 99%
“…For detailed description of the genus see Collin (1961) and Yang & Yang (2004). The adults of Chelifera occur mainly near running waters on riparian vegetation and stones where they prey on Chironomidae, Mycetophilidae and other small insects, while the larvae live in all sorts of freshwater microhabitats, such as sand, gravel, macrovegetation and mosses where they prey on chironomid and simuliid larvae (Horvat 2002;Ivković et al 2012). …”
Section: Introductionmentioning
confidence: 99%